Epidemiology in the Era of Globalization: From Local Outbreaks to World Threats - Andi Nurhalizah Tenriyola (PT. Anagata Sembagi Education, 2025)
Globalization has significantly reshaped the landscape of epidemiology by accelerating the spread of infectious diseases while simultaneously increasing the prevalence of non-communicable diseases. Local outbreaks that were once confined to specific regions can now rapidly evolve into global threats due to advances in transportation, trade, and human mobility. This study employs a qualitative descriptive-analytical approach, utilizing secondary data from scientific literature, WHO reports, and government publications to examine the relationship between globalization and epidemiological transitions. The findings reveal that globalization contributes to a double and even triple burden of disease, encompassing infectious, non-communicable, and environmentally driven health problems. Furthermore, global outbreaks such as SARS, Ebola, Zika, and COVID-19 demonstrate how weak health systems, political decisions, economic inequalities, and the infodemic phenomenon exacerbate the impact of epidemics. The study highlights the urgent need for cross-disciplinary approaches, equitable global health policies, and stronger international cooperation to enhance preparedness and resilience. In conclusion, modern epidemiology must not only focus on biological aspects but also integrate political, social, economic, and digital dimensions in order to protect global health security in the era of globalization.